LEGAL STRENGTHENING OF LOCAL CULTURE-BASED COPYRIGHT ASSETS TO SUPPORT ENTREPRENEURSHIP IN THE TOURISM INDUSTRY - Makkawaru, Zulkifli; Kamsilaniah, Kamsilaniah; Almusawir, Almusawir (Siddiq Institute, 2023)
This research aims to analyze the legal legitimacy of ownership and control of culturally traditional assets in Indonesia, which drive the economicization of cultural wealth through the national tourism industry. Legal weaknesses impede recognition and support to promote the economicization of these cultural assets. The research begins with a review of regulations and policy documentation to understand the philosophical and sociological foundations of the regulation of cultural copyright ownership. The study also examines theoretical aspects of the implementation of the law.Field research is conducted through a series of in-depth interviews with experts and practitioners, both legal professionals and music industry practitioners, collecting data on public understanding through questionnaires. Field data is analyzed quantitatively, while document data and doctrinal studies are analyzed qualitatively.The results of the research indicate a low awareness of locally-based cultural intellectual wealth, as evidenced by the weak appreciation of society, including local governments, in inventorying and registering communal intellectual property assets. The subsequent effect is the weakness in optimizing the commercial value of communal intellectual property, especially in the cultural tourism sector.